Impact of UGT1A1 genetic polymorphism on toxicity in unresectable pancreatic cancer patients undergoing FOLFIRINOX. Issue 2 (12th December 2018) - Shirasu, Hiromichi; Todaka, Akiko; Omae, Katsuhiro; Fujii, Hirofumi; Mizuno, Nobumasa; Ozaka, Masato; Ueno, Hideki; Kobayashi, Satoshi; Uesugi, Kazuhiro; Kobayashi, Noritoshi; Hayashi, Hideyuki; Sudo, Kentaro; et al.
Abstract : Studies have indicated an association between UDP‐glucuronosyltransferase‐1A1 ( UGT1A1 ) genetic polymorphisms and irinotecan‐induced toxicity. We undertook this study to investigate the association between UGT1A1 genetic polymorphisms and toxicity in patients treated with the FOLFIRINOX (comprising oxaliplatin, irinotecan, fluorouracil, and leucovorin) chemotherapy regimen in the JASPAC 06 study. Patients screened for UGT1A1*6 and UGT1A1*28, and treated with either the original FOLFIRINOX (oxaliplatin 85 mg/m 2, irinotecan 180 mg/m 2, leucovorin 200 mg/m 2, bolus 5‐fluorouracil [5‐FU] 400 mg/m 2, and continuous 5‐FU 2400 mg/m 2 ) or a modified FOLFIRINOX (oxaliplatin 85 mg/m 2, irinotecan 150 mg/m 2, leucovorin 200 mg/m 2, and continuous 5‐FU 2400 mg/m 2 ) as first‐line chemotherapy were included. Of 199 patients eligible for this analysis, 79 patients were treated with the original FOLFIRINOX regimen and 120 patients were treated with the modified FOLFIRINOX regimen. In the original FOLFIRINOX group, 54 were UGT1A1 WT, and 25 were UGT1A1 heterozygous type (−/*6, 12 patients; −/*28, 13 patients). In the modified FOLFIRINOX group, 64 were UGT1A1 WT and 56 were UGT1A1 heterozygous type (−/*6, 33 patients; −/*28, 23 patients). In the original FOLFIRINOX group, the incidence of diarrhea was significantly higher among patients with UGT1A1 heterozygous type than among those with UGT1A1 WT and the incidence of leukopenia and diarrhea was significantly higher among patients with UGT1A1 −/*6 than among those with UGT1A1 −/*28. Patients with UGT1A1 heterozygous type, especially those with UGT1A1 −/*6, tended to show a higher incidence rate of severe adverse events, but this was not statistically significant. However, for patients who received the modified FOLFIRINOX, there was no difference in the frequency of adverse events due to UGT1A1 status. In conclusion, patients with heterozygous UGT1A1 polymorphisms treated with the original FOLFIRINOX regimen experienced severe toxicity more frequently than patients with WT UGT1A1 . Abstract : The present study is the first report investigating the association between UGT1A1 genetic polymorphisms, specifically UGT1A1*6 and UGT1A1*28 heterozygosity, and toxicity among Japanese patients with pancreatic cancer treated with FOLFIRINOX.